Analysis On Cooperative Principle And Politeness Principle In Guest Complaining At X Hotel In Kuta-Bali - Sayit Abdul Karim (RETORIKA: Jurnal Ilmu Bahasa, 2016)
Language plays an important role in human life as a medium of communication. The communication between sender and receiver is the activity of conveying ideas, messages, attitude, and mood of both speakers and hearers. This paper attempts to analyze cooperative principle (CP) and politeness principle (PP) in guest complaining at x hotel in Kuta-Bali through a series of conversation at the front desk. The data were gathered from guest’s conversation record book from one of the hotels in Kuta-Bali. The conversations have been transcribed into a written text. The intended data were identified, classified, and then separately analyzed based on cooperative and politeness principle. A qualitative descriptive analysis was employed to analyze CP and PP in the guest complaining as in line with the theories which are proposed by Grice and Leech. The results of analysis show that the receptionist carefully observed both CP and PP, but the guest’s responses might not necessarily comply with those principles for some reasons.  Keywords: Cooperative principle, maxim, speech acts, politeness principle, pragmatics.